Exploring apocalyptica : coming to terms with environmental alarmism - Uekötter, Frank, 1970- (University of Pittsburgh Press, 2018)
Environmental alarmism has long been a political bellwether. Tell me what you think about the green apocalypse, and I'll tell you where you stand on the issues. But as the environmental heydays of the 1970s move into perspective, the time has come for a reassessment. Horror scenarios create a legacy whose effects have largely escaped attention. Based on case studies from four continents and the North Atlantic, ExploringApocalyptica argues for a reevaluation of familiar cliches. It shows that environmentalists were less apocalyptic than commonly thought, and other groups were far more enthusiastic. It traces an interconnection with Cold War fears and economic depressions and demonstrates how alarmism faced limits in the Global South. It also suggests that past horror scenarios impose constraints on ongoing debates. At a time when climate change turns from a scenario into an experienced reality, this book charts paths for an age that may have already moved beyond the peak apocalypse.